SISTEM INFORMASI PEMESANAN MATA FOTO STUDIO BERBASIS DESKTOP - Nadila Triani; Ahmad Suryadi; Anggun Citra Dini Dwi Pupitasari (CV. Denasya Smart Publisher, 2024)
Mata Foto Studio is a rapidly growing Photo Studio located in the city of Jakarta. Providing types of photo category choices according to the customer's wishes, while the problem that occurs in this studio is the ordering system and reports that still use Microsoft Excel. From the results of the analysis carried out, the author intends to help the problems that exist in Mata Foto Studio, namely by creating a desktop-based information system. The tools used in building the system, namely Context Diagram, and DFD. The development of this information system uses the PHP programming language and uses the MySql database. With the desktop-based Mata Foto Studio ordering information system, it is hoped that it will facilitate the ordering process, transactions, and report data processing. This makes it easier for the customer to place an order.